Lingüística mochica: cuestiones etimológicas y analíticas - Eloranta, Rita (2019)
In this article, I examine some previously proposed etymologies of words of Mochica origin. In addition, I discuss certain hispanicisms that would be better understood when seen as stemming from Mochica. To this end, I also discuss diverse grammatical aspects of the extinct Mochica language: nominal possession, numeral classification, spatial relation markers, nominalization and future paradigms. The reflections I offer here are based on José Antonio Salas’s (2012) book entitled Etimologías mochicas.